Multiple sclerosis recovery of function and neurorehabilitation - Kesselring, Jürg; Comi, G. (Giancarlo), 1947-; Thompson, Alan J., M. D. (New York : Cambridge University Press, 2010)
"Recent developments in basic and applied science have led to better understanding of disease mechanisms and more efficient therapies for multiple sclerosis. The most effective way of managing these patients is through a carefully planned neurorehabilitation programme. The main aims are to reduce disability and handicap and improve functions through effective training, stimulating activity and social participation. As the first text on recovery of function and neurorehabilitation in MS, this book focuses on mechanisms of recovery, application of neuroplasticity to therapeutic interventions, and determination of the efficiency of these interventions. Basic principles of neurorehabilitation in MS are described, as well as techniques for treating specific syndromes which may occur in MS. Written and edited by leading clinicians and researchers, the book achieves an excellent balance between basic science, pathophysiology, and clinical rehabilitation. An essential resource for clinicians and therapists treating patients with multiple sclerosis, neurophysiologists, and health care advisors"--Provided by publisher.